PENGAWASAN ATASAN LANGSUNG TERHADAP DISIPLIN KERJA PEGAWAI KANTOR DINAS TENAGA KERJA DAN KEPENDUDUKAN KOTA BANDA ACEH - Yoyon Safrianto; Muzakir Muzakir (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2019)
The awareness of discipline is something very important for any organization. One way to improve the awareness of discipline is through being under the immediate. This reseacrh to know the supervision of superior directly to the awareness of discipline the office of labor and population city Banda Aceh. Respondents this research consisting of employees and each head part on any part of which is in these agencies. Data collection is done by distributing questionnaires containing questions relating to monitoring the direct and the awareness of discipline. Data on anaslisis using the statistics multiple linear regression analysis. The result showed that pengasan immediate superior which includes monitoring, examination, and judgment influential positive on the awareness of discipline. The koefesien terminated (r2) of 0,217 means that 21,7 percent the awareness of discipline on these agencies influenced by monitoring, check and assess the as a form of supervision immediate superior. The rest of 78.3 percent longer had other factors besides monitoring the immediate superior .The results of testing statistics show value F count larger had than the F table at the belief 95 percent. Hypothesis Ha accepted, on the other hand hypothesis H0 rejected, supervision and monitoring of immediate superior, examination, and assessment.